Density of The Crested Black Macaque (Macaca nigra) and Habitat Quality in Tangkoko, Bitung, North Sulawesi - Edyson Maneasa; Suddin Simandjuntak; Yermia Semuel Mokosuli (Jurnal Biologi Tropis, 2021)
The Crested black macaque (Macaca nigra) is an endemic species to the Sulawesi Island, limited distribution, and Critically Endangered on the IUCN red list. The population density in the Tangkoko Conservation Forest Management Unit (CFMU) has decreased significantly due to habitat destruction and hunting. Existing data are based on the study in the northern part of Tangkoko. Currently, data from the southern is urgently needed so that population data covers the entire area, including to identify the habitat quality. The aims of this study was to (1) analyze the population density level of Crested black macaque at the Tangkoko CFMU, (2) identify the habitat characterize of Crested black macaque at the Tangkoko CFMU, (3) analyze the correlation between Crested black macaque density and habitat quality at the Tangkoko CFMU. The study was conducted from January to March 2020 in the sothern of Tangkoko CFMU, North Sulawesi. The data collection on the density of Crested black macaque is done by animals directly inventorying through surveys in the field. Observations are carried out by walking at speeds of 1 - 1.5 km / h on each track and stopping at every 100 m to observe the surroundings. Data recorded is the number of individuals found using the line transect method. Vegetation data collection method used is habitat quality data collection carried out by making sample plots measuring 25 m x 25 m for tree level observations in lines with each distance between plots is 250 m. Data recorded for dominance of vegetation are species names, number of individuals, and diameter at breast height of trees. The results showed that (1) the population density level of Crested black macaque was 15 individuals/km2. The highest amount of density is found on the D4 was 72 individu/km2, the lowest on D1, D5, D6, and D7 with no macaques; (2) vegetation analyzed at 45 plots were important value index with the highest value of 86,95 is Ficus variegata on line D7 for tree level, and Theobroma cacao for pole level with highest value of 120,80 on line D4; (3) the correlation between density of Crested black macaque and habitat quality that shows a positive value based on the Pearson correlation test. Further research is needed to determine the relationship between population density, habitat disturbance, and hunting pressure.